Competence approach in the design of purpose of training of language teaching - Катеруша, О. В. (Pedagogy of Higher and Secondary Education, 2013)
Katerusha O. V. Competence approach in the design of purpose of training of language teaching. The article reveals ways of communicative knowledge development, skills and methods of communicative behavior that is the purpose of the tactical and operational levels of competent approach.